A Literature Analysis of Differentiated Instruction as a Learning Management Strategy in Physical Education - I Kadek Angga Prabawanata; Kadek Yogi Parta Lesmana; I Made Satyawan (Journal of Physical Education Health and Sport, 2025)
This study aims to analyze differentiated instruction as a learning management strategy in Physical Education, Sports, and Health (PESH) through a literature review approach. Education plays a crucial role in developing high-quality human resources; however, learning challenges such as declining educational quality, low student motivation, and diverse learner characteristics remain prevalent, particularly in PESH learning. Differentiated instruction is considered a relevant pedagogical approach to address these challenges by adjusting learning content, processes, and products according to students’ readiness levels, interests, and learning profiles. This study employed a descriptive literature review method. Data were collected through a systematic search of scientific articles, reference books, and academic journals published within the last five to ten years using databases such as Google Scholar and PubMed. The selected literature was analyzed through categorization, comparison, and synthesis to identify patterns and key findings related to the implementation of differentiated instruction in PESH learning. The findings indicate that differentiated instruction has a positive impact on student motivation, engagement, and learning outcomes in PESH. The approach strengthens teachers’ roles as facilitators and learning managers who are responsible for planning, organizing, implementing, and evaluating learning activities in a flexible yet structured manner. Furthermore, differentiated instruction aligns with the principles of the Merdeka Curriculum, which emphasizes student-centered and inclusive learning. In conclusion, differentiated instruction is an effective learning management strategy that supports inclusive, engaging, and sustainable PESH learning environments.